A White-Light-Emitting Small Molecule: Synthesis, Crystal Structure, and Optical Properties - Sin-Kai Fang; Hsing-Yang Tsai; Jiun-Wei Hu; Kew-Yu Chen (International Journal of Photoenergy)
A white-light-emitting small molecule (1) was synthesized and characterized by single-crystal X-ray diffraction. Compound 1 undergoes an excited-state intramolecular proton transfer (ESIPT) reaction, resulting in a tautomer that is in equilibrium with the normal species and exhibiting a dual emission that covers almost all of the visible spectrum, and consequently generates white light. Furthermore, the geometric structures, the frontier molecular orbitals (MOs), and the potential energy curves for 1 in the ground and the first singlet excited state were fully rationalized by density functional theory (DFT) and time-dependent DFT calculations. The results show that the forward ESIPT and backward ESIPT may happen on the same timescale, enabling the excited-state equilibrium to be established.